Does normative multiculturalism foster or threaten social cohesion?. (March 2020) - Watters, Sara Morgan; Ward, Colleen; Stuart, Jaimee
Abstract: The study advances a tri-dimensional model of multiculturalism that highlights the importance of perceived societal norms, i.e., the extent to which one's society is perceived as characterized by culturally diverse groups in contact with one another (Multicultural Contact, MC), a widespread appreciation of cultural diversity (Multicultural Ideology, MI), and multicultural policies and practices (MPP) to support and accommodate that diversity. A community sample of 143 Hispanics and 141 non-Hispanic Whites in the United States completed an online survey that examined perceptions of normative MC, MI and MPP as predictors of trust and national attachment, key indicators of social cohesion. The results indicated that MI, MC and MPP predict greater national attachment and that MI predicts greater trust; however, the positive effects of MI are limited to Hispanics and not found for Whites. The findings point to the conclusion that normative multiculturalism is more likely to foster than to threaten social cohesion.